2007
DOI: 10.1002/jclp.20380
|View full text |Cite
|
Sign up to set email alerts
|

Past and recent deliberate self‐harm: Emotion and coping strategy differences

Abstract: Only limited information on nonsuicidal deliberate self-harm behavior among nonclinical populations is available, and it is unclear whether coping and emotional difficulties remain among those with a past history of self-harm behavior. The purpose of this study is to examine emotions and coping strategies among three nonclinical groups with a recent, past, and no history of nonsuicidal deliberate self-harm behavior. College students completed self-report measures of self-harm behavior, suicidal thoughts, emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
87
2
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 31 publications
9
87
2
3
Order By: Relevance
“…Only one study found no such difference [110]. In three studies involving young adults [11,26,67] and in three studies involving adult samples of a large age range [27,43,49], there was no gender difference found. One study yielded no gender effect on recurrence of deliberate self-harm [23].…”
Section: Sociodemographic Correlates and Risk Factorsmentioning
confidence: 67%
See 1 more Smart Citation
“…Only one study found no such difference [110]. In three studies involving young adults [11,26,67] and in three studies involving adult samples of a large age range [27,43,49], there was no gender difference found. One study yielded no gender effect on recurrence of deliberate self-harm [23].…”
Section: Sociodemographic Correlates and Risk Factorsmentioning
confidence: 67%
“…Assessment categories: 1=no information; 2=case ascertainment/medical records; 3=standardized clinician-administered rating; 4=ad hoc interviews; 5=validated interviews; 6=single items, self-report/interview; 7=ad hoc questionnaire; 8=validated questionnaire (assignment to assessment category is given in parentheses if information is insufficient to judge). [23] LT (12 months) +++ Highest recurrence of DSH for age group 25-54 years Sex [11,26,27,49,52,67] CS 00/(++) 6 studies found no sex differences in adults [107] 1 study found more females among medical patients treated for self-harm [45,87,92,93,102,109,110] 6 studies on adolescents found a higher prevalence in females (2:1 to 4:1); 1 study on adolescents found no sex differences [69] LT (1-2 years) 000 Not predictive of DSH recurrence [23] LT (12 months) Unemployment [78,99] CS +++ [90] LT (6 months) Predictive of DSH recurrence [23] LT (12 months) No partnership [78] CS +++ [90] LT (6 months) Predictive of DSH recurrence (except when widowed) [23] LT (12 months factor. "+" indicates positive evidence from only one crosssectional study.…”
Section: Taxonomy Of Correlates and Risk Factorsmentioning
confidence: 99%
“…Within this, it is paramount to appreciate that transitions are a dynamic process. Those who have self-harmed may not always continue to do so; selfharming may discontinue across time, or individuals may have periods free from harming/ thoughts of harming (Brown et al, 2007;Wadman et al, 2016). Therefore, transitions do not necessarily follow a uni-directional progression from ideation to enactment.…”
Section: Self-harm Ideation Versus Self-harm Enactmentmentioning
confidence: 99%
“…previous research has operationalised 'recent' using a range of arbitrarily defined cut-offs (Brown et al, 2007). It is unclear whether adopting an alternative recency threshold would affect the pattern of significant findings.…”
Section: Coping Self-harm Ideation and Enactment 17mentioning
confidence: 99%
“…Current findings demonstrate health-compromising behaviours -such as substance use and abuse, disordered eating, and cutting -were coping strategies for the young women to lessen their focus on IPV and to provide emotional release. Researchers have studied individuals' use of health-compromising behaviours to cope with stress and distress (Andover, Pepper, & Gibb, 2007;Brown, Williams, & Collins, 2007;Evans, Hawton, & Rodham, 2005;Walker, 2007). Furthermore, several authors describe the use of health-compromising behaviours as coping within the context of an IPV relationship, such as the use of alcohol and illicit drugs (Bennett & O'Brien, 2007;Golinelli et al, 2008;Stalans & Ritchie, 2008;Sullivan & Holt, 2008;Wiemann et al, 2000), the use of psychotropic medication (Romans et al, 2008), and self-harm behaviours such as cutting and burning (Health Canada, 2002a).…”
Section: Coping To Change Their Responses To Ipvmentioning
confidence: 99%